Basics of dairying in the Tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Dairy technology in the Tropics and Subtropics by J C T van den Berg 1988 290pp ISBN 90 220 0927 Pudoc, PO Box 4, 6700 AA Wageningen THE NETHERLANDS